Analisis Website Unit Pengembangan Kewirausahaan dan Karier Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Fawaid As’ad; Hery Afriayadi (Lembaga Pengembangan Kinerja Dosen, 2025)
The website of the Career and Entrepreneurship Development Unit (UPKK) at the State Islamic University of Sulthan Thaha Saifuddin Jambi serves as a digital platform that provides information and services for students and alumni in the context of career and entrepreneurship development. However, the effectiveness of this website still faces various challenges, both technical and non-technical. This report aims to analyze the quality and performance of the UPKK website based on usability aspects, user interface design, navigation structure, content relevance, and responsiveness across various devices. The research was conducted through direct observation, interviews with administrators, and a literature review on web-based information system development standards.The analysis results indicate that the UPKK website does not fully meet visual comfort standards, has unintuitive navigation, outdated content, and lacks optimization for mobile accessibility. Additionally, content management is carried out manually without the support of a Content Management System (CMS), resulting in slow information updates.Based on this evaluation, this report provides several development recommendations, including the use of a CMS such as WordPress, a redesign of the user interface based on UI/UX principles, and the formation of a content management team with a routine evaluation schedule. It is expected that the website’s development can enhance UPKK’s service delivery and increase student and alumni engagement in career and entrepreneurship programs.